2012
DOI: 10.1016/j.jvs.2012.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Suprarenal graft fixation in endovascular abdominal aortic aneurysm repair is associated with a decrease in renal function

Abstract: In contrast to previous studies, this study suggests that suprarenal endograft fixation in elective EVAR is associated with a drop in eGFR at 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 36 publications
1
53
1
2
Order By: Relevance
“…The scope of the current analysis was not to associate EVAR-related AKI with outcome, as we have recently reported on this association(7). important observation is that EVAR can lead up to a 6 unit decrease in eGFR per annum, which is significantly more pronounced than the estimated loss of renal function compared to the general population, as we have previously shown (37). This later loss in renal function can lead to further cardiovascular morbidity over the long term.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The scope of the current analysis was not to associate EVAR-related AKI with outcome, as we have recently reported on this association(7). important observation is that EVAR can lead up to a 6 unit decrease in eGFR per annum, which is significantly more pronounced than the estimated loss of renal function compared to the general population, as we have previously shown (37). This later loss in renal function can lead to further cardiovascular morbidity over the long term.…”
Section: Discussionmentioning
confidence: 70%
“…This has been shown to be superior to previous GFR estimates in patients with cardiovascular disease (38). We have not included serum creatinine in our multivariate analyses, as it underestimates renal dysfunction -especially in older populations with a significant cardiovascular burden, as we have previously discussed (6,29,39).…”
Section: Discussionmentioning
confidence: 98%
“…Another limitation of the study is the low number of AKIþ patients in the EVAR group, which negatively affects a statistical comparison between the two types of intervention. Finally, many potentially interesting data that have been evaluated in previous works are lacking: intensive care unit stays, 18 postoperative hemodynamic parameters, 11 intraoperative and perioperative fluid management, 19,20 contrast agent use, 5 blood losses, 5 impact of suprarenal fixation, 21 and longterm assessment of renal function. 22 A detailed report of all these parameters would have added many points of consideration to the discussion.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that 18% of patients undergoing EVAR will have a clinically significant increase in their serum creatinine (SCr) after 1 year (9). Previous studies have also demonstrated a greater decrease in eGFR for patients who undergo EVAR for the first year compared with the general population (6,10). EVAR is now offered electively in younger patients and it is therefore important to be aware of the long-term renal implications.…”
Section: Introductionmentioning
confidence: 99%
“…The latter will deviate from normal values only after at least one-half of the functioning renal mass has been affected (11). Two studies offer sufficiently long follow-up but only included a small number of patients after the first 2 years (12,13) and did not differentiate between suprarenal and infrarenal device fixation during EVAR; suprarenal fixation may adversely affect renal function (10). In addition, there are no high-quality comparisons between EVAR, OAR, and similar populations without aneurysmal disease.…”
Section: Introductionmentioning
confidence: 99%